PEMANFAATAN MATERIAL LOKAL DALAM PEMBUATAN ASPAL PORUS TIPE AC-WC YANG AMAN DAN RAMAH LINGKUNGAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
Surface of highway pavement is wet during rain and drowned by stormwater. This situation can makes slip of vehicle wheels and causes an accident. Porous asphalt is a new generation in flexible pavement. Porous charactheristic can be obtained by using less fine aggregates comparing the normal one so it has more voids. We can expect the pavement has higher skid resistance and its voids can be functioned as drainage in mix. This type of pavement developement also strongly depends on availability of the approriate local material for that we can produce a good performance porous asphalt which is described in this paper. Consideration of so many problems can be taken apart, the research is limited in modification design of asphalt concrete wearing course using porous asphalt mix exploits South Sumatera aggregates. After investigatives classification of aggragates, the fine aggregates (sand) can be reduced significantly to obtain a large amount of voids by 6.1% asphalt used. However, this porous structure also causes defect, mainly the stability degradation in mix. So the future research will continue to formularize a better stability performance from pavement variety expected